Perforated tumours in the gastrointestinal tract: CT findings and clinical implications - Kim, S W (The British Institute of Radiology., 2012)
Perforation usually requires emergency surgery and may affect the prognosis of patients with gastrointestinal tumours. Accurate pre-operative diagnosis of these conditions is important because proper management such as curative surgical treatment may be needed. The aims of this article are to illustrate CT appearances of perforated tumours of the gastrointestinal tract and to discuss their impact on clinical management.